2007
DOI: 10.1016/j.beproc.2006.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive responding on the peak-interval procedure

Abstract: The pattern of responding on a peak-interval timing task allows one to make inferences regarding the sources of variation that contribute to interval timing behavior. Non-temporal factors such as impulsivity may impact the validity of these inferences. Rats were trained on a 15s peak-interval procedure (PI) or a mixed 15s behaviorally dependent variable-interval, 15s peak-interval procedure (bdVIPI) for an extended number of sessions. Extended training on the PI revealed a bi-modal distribution in the times at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 57 publications
7
39
2
Order By: Relevance
“…Pigeons thus showed increased sharpening of peak-time curves over successive sessions of probe testing, produced primarily by a decline in responding after the FI. This finding replicates similar observations recently made with pigeons (Kirkpatrick-Steger, Miller, Betti, & Wasserman, 1996) and with rodents (Balci et al, 2009;Kaiser, 2008;Matell & Portugal, 2007).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Pigeons thus showed increased sharpening of peak-time curves over successive sessions of probe testing, produced primarily by a decline in responding after the FI. This finding replicates similar observations recently made with pigeons (Kirkpatrick-Steger, Miller, Betti, & Wasserman, 1996) and with rodents (Balci et al, 2009;Kaiser, 2008;Matell & Portugal, 2007).…”
Section: Discussionsupporting
confidence: 94%
“…However, recent research has suggested that different leaming processes are responsible for pre-and postpeak performance (Balci et al, 2009;Kaiser, 2008;Kirkpatrick-Steger et al, 1996;Matell & Portugal, 2007). Because prepeak responding reaches asymptote much faster than does postpeak responding, the asymmetry in response curve flattening in the current research might be due to differential effects on leaming.…”
Section: Gênerai Discussioncontrasting
confidence: 48%
“…To further assess the changes of the performance over the light/dark cycle, we analyzed the Actual Inter-Trials (AIT) durations between two consecutive trials. These intervals occur because of the delay of the mouse to initiate a trial and have been used as a measurement of impulsivity (Matell and Portugal, 2007). A significant difference was found between genotypes along the 24 h and was accentuated during the dark phase (Figure 4f).…”
Section: Taar1 and Nmda S Espinoza Et Almentioning
confidence: 84%
“…This is unusual because previous studies have shown that a reduction in DRL efficiency is usually accompanied by an increase in burst responding, a pattern that can be induced by administration of psychostimulants (e.g., Cheng et al 2006a). The prevailing explanations for this pattern of responding are either that these drugs accelerated the speed of an internal clock and/or increased impulsivity, which in turn would decrease response efficiency (e.g., Meck 1996;Wiley et al 2000;McAuley et al 2006;Matell and Portugal 2007). Both of these explanations are likely to be inappropriate in the present situation because of the observation that SUP-male rats display the same temporal accuracy with increased precision compared with CON-male rats when assessed in other reproduction tasks such as the peak-interval procedure (e.g., Meck and Williams 1997a;Cheng et al 2006b;Cheng and Meck 2007).…”
Section: Discussionmentioning
confidence: 99%